2019
DOI: 10.1142/s1088424619500238
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial photodynamic therapy against Staphylococcus aureus using zinc phthalocyanine and zinc phthalocyanine-integrated TiO2 nanoparticles

Abstract: Antibiotic resistance is an increasing healthcare problem worldwide. In the present study, the effects of antimicrobial photodynamic therapy (APDT) of ZnPc and ZnPc-integrated TiO2 nanoparticles (ZnPc-TiO[Formula: see text] were investigated against Staphylococcus aureus. A light emitting diode (LED) (630–700 nm, 17.4 mW/cm[Formula: see text] was used on S. aureus at different light doses (8 J/cm2 for 11 min, 16 J/cm2 for 22 min, 24 J/cm2 for 33 min) in the presence of the compounds under the minimum inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
10
0
1
Order By: Relevance
“…Two recently published studies indicate that the combination of TiO 2 with phthalocyanines and subphthalocyanines raises the effectiveness of antimicrobial photodynamic therapy. On the one hand, Tunçel et al showed that the application of Zn(II) phthalocyanine with (4-carboxyphenyl)ethynyl moieties alone or after integration with TiO 2 NPs leads to very similar photocytotoxicity results [61]. On the other hand, the cellular uptake of these molecules was substantially lower when phthalocyanine was combined with titanium dioxide.…”
Section: Tio 2 Nanoparticles Combined With Phthalocyaninesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recently published studies indicate that the combination of TiO 2 with phthalocyanines and subphthalocyanines raises the effectiveness of antimicrobial photodynamic therapy. On the one hand, Tunçel et al showed that the application of Zn(II) phthalocyanine with (4-carboxyphenyl)ethynyl moieties alone or after integration with TiO 2 NPs leads to very similar photocytotoxicity results [61]. On the other hand, the cellular uptake of these molecules was substantially lower when phthalocyanine was combined with titanium dioxide.…”
Section: Tio 2 Nanoparticles Combined With Phthalocyaninesmentioning
confidence: 99%
“…It is worth noting that a bactericidal effect against S. aureus of subphthalocyanine was observed at 24 J/cm 2 , whereas the subphthalocyanine-TiO 2 hybrid material was active at 16 and 24 J/cm 2 of light doses, which suggests the increased photoactivity of the material as compared to its components alone. Moreover, both subphthalocyanine and subphthalocyanine-TiO 2 hybrid material were active against Gram-negative strain E. coli at 30 J/cm 2 of light dose [61,62]. Mantareva et al studied the photodynamic activity of Zn(II) phthalocyanine salt containing 3-dodecylpyridyloxy moieties (ZnPcDo) adsorbed on TiO 2 anatase NPs in vivo against methicillin-resistant Staphylococcus aureus (MRSA) and Salmonella enteritidis [63].…”
Section: Tio 2 Nanoparticles Combined With Phthalocyaninesmentioning
confidence: 99%
“…Two recently published studies indicate that the combination of TiO2 with phthalocyanines and subphthalocyanines raises the effectiveness of antimicrobial photodynamic therapy. On the one hand, Tunçel et al showed that the application of Zn(II) phthalocyanine with (4-carboxyphenyl)ethynyl moieties alone or after integration with TiO2 NPs leads to very similar photocytotoxicity results [61]. On the other hand, the cellular uptake of these molecules was substantially lower when phthalocyanine was combined with titanium dioxide.…”
Section: Modifications Of Tio2 With Photosensitizers Aiming To Improvmentioning
confidence: 99%
“…It is worth noting that a bactericidal effect against S. aureus of subphthalocyanine was observed at 24 J/cm 2 , whereas the subphthalocyanine-TiO2 hybrid material was active at 16 and 24 J/cm 2 of light doses, which suggests the increased photoactivity of the material as compared to its components alone. Moreover, both subphthalocyanine and subphthalocyanine-TiO2 hybrid material were active against Gram-negative strain E. coli at 30 J/cm 2 of light dose [62,76]. Mantareva et al studied the photodynamic activity of Zn(II) phthalocyanine salt containing 3-dodecylpyridyloxy moieties (ZnPcDo) adsorbed on TiO2 anatase NPs in vivo against methicillin-resistant Staphylococcus aureus (MRSA) and Salmonella enteritidis [63].…”
Section: Modifications Of Tio2 With Photosensitizers Aiming To Improvmentioning
confidence: 99%
“…In another report, the photosensitizer zinc phthalocyanine was integrated with TiO 2 nanoparticles and investigated for its use as antimicrobial photodynamic therapy against S. aureus. The nanoconjugate showed promising phototoxicity towards S. aureus [17]. Based on a literature survey, MB and metallic NPs can be employed in combination to eliminate microorganisms using light irradiation [18,19].…”
Section: Introductionmentioning
confidence: 99%